Słownictwo rzemiosł skórzanych w XIX-wiecznych ukraińsko-niemieckich słowniczkach Ilki Magury - Skurzewska, Agata (Studia Ukrainica Posnaniensia, 2024)
The aim of the article is to present the lexicon of leather crafts recorded in Ilko Magura’s Ukrainian-German dictionaries dating back to the 1860s. The Ukrainian language material came from the Zhovkva district, within which the author’s hometown, Uhniv, was located. The inhabitants of this village had been engaged in leather crafts for centuries, primarily tanning and shoemaking. The 19th-century shoes called uhnivtsi were popular and famous throughout Galicia. Dictionaries are dominated by vocabulary related to the process of leather tanning and the subsequent production of shoes. It includes the names of craftsmen, tools and devices, shoe parts, materials and substances, for example, as well as activities. Through these records we learn the specialist vocabulary of leather crafts presented in the linguistic reality of the largest shoemaking center in 19th-century Galicia.